Treatment-related symptom severity and occurrences among oncology adults in Australia - Violeta Lopez; Phoebe Williams; David Larkin (Elsevier, 2015)
Objective: Cancer treatments cause a range of distressing symptoms that can be well managed with pharmacological and nonpharmacological interventions. Treatment-related symptom screening and management by health care professionals is required to provide appropriate guidance to help patients to complete successfully their treatment regimen and achieve the best possible outcomes for patients. The aims of this study were to explore treatment-related symptom severity and occurrences among oncology adults in Australia and compare the results with the Chinese and Filipino studies. Methods: A cross-sectional descriptive survey of 84 adult patients over 18 years of age undergoing chemotherapy (CT) and/or radiotherapy (RT) in the Radiation Oncology and Medical Oncology Departments in one public teaching hospital in Canberra, Australia using the 25-item treatment-related symptom checklist (TRSC) was used in this study. Results: Six symptom clusters emerged from combining the 25 symptoms. Patients receiving CT experienced highest fatigue symptom occurrences (95.8%) and greater symptom severity (mean = 2.59) for fatigue symptom cluster for patients receiving a combination of CT-RT. Australians treatment-related symptom severity and occurrences were higher compared with the Filipino and Chinese adult cancer patients. Conclusions: Nurses in oncology settings are uniquely placed to assess patients' therapy-related symptoms that will assist them to target education to cancer patients' individual needs. For all types of cancer, it is important to assess treatment-related symptoms and to provide the most appropriate interventions in consideration to the patients' preferences.